2020
DOI: 10.1177/1086026620933915
|View full text |Cite
|
Sign up to set email alerts
|

Learning Organization for Corporate Social Responsibility Implementation: Unravelling the Intricate Relationship Between Organizational and Operational Learning Organization Characteristics

Abstract: Because corporate social responsibility (CSR) is potentially beneficial for companies, it is important to understand the factors that improve a company’s CSR practice. Scholars hypothesize that facilitating learning organization characteristics, which are divided in characteristics at the organizational and the operational level, may improve CSR implementation. These characteristics stimulate companies and their members to be critical, learn from the past, and embrace change, but there is limited empirical evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…Third, this work may contribute at the micro level of CSR research. The past literature has an emphasis on the implementation of CSR (Osagie et al, 2020), and impacts of CSR on organizational performance in response to the call for more caring about stakeholder benefits and sustainability (Farrington, 2017;Gu et al, 2013;Javed et al, 2020;Kim et al, 2017a;Liao & Zhang, 2020;Serra-Cantallops et al, 2018). These findings offer robust evidence on the impacts of CSR on employee green behavior and task performance, as well as enriching CSR research at a micro level (Aguinis & Glavas, 2019;Ahmed et al, 2020;Boan & Dedeolu, 2020;Cheema et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 79%
“…Third, this work may contribute at the micro level of CSR research. The past literature has an emphasis on the implementation of CSR (Osagie et al, 2020), and impacts of CSR on organizational performance in response to the call for more caring about stakeholder benefits and sustainability (Farrington, 2017;Gu et al, 2013;Javed et al, 2020;Kim et al, 2017a;Liao & Zhang, 2020;Serra-Cantallops et al, 2018). These findings offer robust evidence on the impacts of CSR on employee green behavior and task performance, as well as enriching CSR research at a micro level (Aguinis & Glavas, 2019;Ahmed et al, 2020;Boan & Dedeolu, 2020;Cheema et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 79%
“…Social power was also demonstrated in transdisciplinary research projects within the social sciences where it was found that researchers, due to their higher social and educational status, would often intimidate other actors and impact the group's ability to establish shared mental models and visions (Ely et al, 2020;Roux et al, 2017). In business and management studies, top leadership determined a project team's course of action and overall performance measures (Osagie et al, 2020;Pallett & Chilvers, 2013;Weissbrod & Bocken, 2017). Responses to these power imbalances ranged from embedding rules and policies around participation and decisionmaking processes (Heikkila & Gerlak, 2019) to strategically timing when top leadership were brought in to review a project (Weissbrod & Bocken, 2017).…”
Section: Power and Participationmentioning
confidence: 99%
“…However, broadening organizational perspectives and collaborating with diverse stakeholders involves inherent political and process-related tensions stemming from a resistance to change, competing motivations, lack of trust, and disciplinary-specific language (Bechky, 2003;Edmondson & Nembhard, 2009;Roux et al, 2017). Learning has been identified as a key organizing process for overcoming the challenges that arise in collaborative action for sustainability (Oelze et al, 2016;Osagie et al, 2020;Roux et al, 2017). Improving an organization's ability to learn has been directly linked to their ability to adapt and change (Edmondson & Moingeon, 1998;Edmondson & Nembhard, 2009); both of which are necessary for organizations responding to sustainability (Linnenluecke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the attempts to incorporate the strategically objective point through formulating the number of goals to be achieved within the visions, professional skills expressed into measuring the health procedure of policy making need to incorporate in employing the effective strategy together with appropriate means in expanding the social and individual balance along with planning management. In this view, the strategic appointment in getting accessibility in transmitting the information relevant to the customer need in the basis of the entire methods on expressing the corporate governance should bring along with the strategic organisation plan formulated in the basis of emphasising the organisational sustainability technique [49,50]. As such, the essentials of strategic competency as the culture in expanding the social elements with organisational development would Corporate Social Responsibility be the key assessment of determining the policy making together with establishing the management procedure structured into the technical based governance.…”
Section: Expanding Professional Competence-based Knowledge Skillsmentioning
confidence: 99%